The effects of aging on Amyloid-β42-induced neurodegeneration and regeneration in adult zebrafish brain. Issue 1 (1st January 2017) - Bhattarai, Prabesh; Thomas, Alvin Kuriakose; Zhang, Yixin; Kizil, Caghan
ABSTRACT: Alzheimer disease is the most prevalent neurodegenerative disease and is associated with aggregation of Amyloid-β42 peptides. In mammals, Amyloid-β42 causes impaired neural stem/progenitor cell (NSPC) proliferation and neurogenesis, which exacerbate with aging. The molecular programs necessary to enhance NSPC proliferation and neurogenesis in our brains to mount successful regeneration are largely unknown. Therefore, to identify the molecular basis of effective brain regeneration, we previously established an Amyloid-β42 model in adult zebrafish that displayed Alzheimer-like phenotypes reminiscent of humans. Interestingly, zebrafish exhibited enhanced NSPC proliferation and neurogenesis after microinjection of Amyloid-β42 peptide. Here, we compare old and young fish to address the effects of aging on regenerative ability after Amyloid-β42 deposition. We found that aging does not affect the rate of NSPC proliferation but reduces the neurogenic response and microglia/macrophage activation after microinjection of Amyloid-β42 in zebrafish, suggesting an important link between aging, neuroinflammation, regenerative neurogenesis and neural stem cell plasticity.